2018
DOI: 10.1007/s10198-018-0996-9
|View full text |Cite
|
Sign up to set email alerts
|

Pricing of HPV vaccines in European tender-based settings

Abstract: HPV vaccine procurement is widely used across Europe. The fourfold decrease in the average tender-based prices compared to list prices confirms the potential of tendering as an efficient cost-containment strategy, thereby expanding the indications for cost-effective HPV vaccination to previously ineligible target groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Similarly, Qendri et al has retrieved the procurement notices and awards from 15 European countries, and found that prices of first-generation HPV vaccines decreased from USD 122.2 (EUR 101.8) in 2007 to USD 34.1 (EUR 28.4) in 2017, whereas the average dose price of the nine-valent vaccine in 2016–2017 was USD 58.9 (EUR 49.1). The unit prices were, respectively, in the range of USD 9.0 (EUR 7.5) and USD 41.3 (EUR 34.4) higher for the four-valent and nine-valent vaccines than for the two-valent vaccine [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Qendri et al has retrieved the procurement notices and awards from 15 European countries, and found that prices of first-generation HPV vaccines decreased from USD 122.2 (EUR 101.8) in 2007 to USD 34.1 (EUR 28.4) in 2017, whereas the average dose price of the nine-valent vaccine in 2016–2017 was USD 58.9 (EUR 49.1). The unit prices were, respectively, in the range of USD 9.0 (EUR 7.5) and USD 41.3 (EUR 34.4) higher for the four-valent and nine-valent vaccines than for the two-valent vaccine [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…On an annual basis, the contract volume was associated with a decrease in the per-dose price of USD 13.21 (EUR 11.0) per 100,000 doses per year. Additionally, regional level procurement of vaccines resulted in higher unit prices, USD 10.68 (EUR 8.9) per dose when compared to the procurement at the national level [ 18 ]. Similarly, offers received from both manufacturers lowered the unit price of vaccine by USD 5.40 (EUR 4.5) compared to procurement that received only one offer [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…and are heavily examined against many diverse pathogens including influenza A, Norovirus, Chikungunya virus, cytomegalovirus, rotavirus and Group A Streptococcus, to name a few [ 8 , [12] , [13] , [14] , [15] ]. However, the production and purification of existing commercial VLPs is challenging, making them comparatively expensive vaccines [ 11 , 16 , 17 ]. VLPs can be expressed in a variety of eukaryotic and prokaryotic systems, ranging from mammalian and insect cells to microbial, yeast and plant based systems [18] .…”
Section: Introductionmentioning
confidence: 99%
“…When considering both-sex vaccination evaluations, it should be noted that the context is usually female-only vaccination as the comparator because most countries introduced female-only vaccination first; cost-effectiveness will thus be dependent on the vaccine coverage in girls and vaccine price. Recent evidence shows that list prices are rarely paid in national or regional vaccination programs [33]. The actual price paid for vaccines at a regional or country level is often an outcome of confidential tender negotiations and may not be available to use in an analysis; in this situation it is recommended that threshold analysis be performed to determine the maximum price that should be paid.…”
Section: Domain 1 Reporting Modelled Evaluations Of Hpv Vaccination mentioning
confidence: 99%
“…Very little work modelling vaccination of older people has been performed thus far. However, the original evaluations of female HPV vaccination in relation to the optimal age of catch-up are very relevant to evaluations of untargeted vaccination to older ages [33]. Some of the original catch-up vaccination modelling literature was difficult to interpret because a wide age range of vaccination was modelled.…”
Section: Domain 2 - Additional Issues In Reporting Vaccination In Oldmentioning
confidence: 99%